2019
DOI: 10.17116/kardio201912051386
|View full text |Cite
|
Sign up to set email alerts
|

Early neurological outcomes after simultaneous coronary artery bypass surgery and carotid endarterectomy

Abstract: Научно-исследовательский институт комплексных проблем сердечно-сосудистых заболеваний, Кемерово, Россия РЕЗЮМЕ Цель исследования-оценка госпитальных неврологических исходов после коронарного шунтирования (КШ) в сочетании с каротидной эндартерэктомией (КЭЭ) в зависимости от симптомности церебрального атеросклероза. Материал и методы. Оценены неврологические исходы у 42 пациентов с мультифокальным атеросклерозом (МФА). Критерий включения: пациенты, планируемые на сочетанное хирургическое вмешательство (унилатера… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Although this procedure is not always complicated by traumatic brain injury (stroke), it may cause a less pronounced, diffuse lesion that later leads to cognitive decline (Weimar et al, 2017;Maleva et al, 2020). Previous studies have shown that patients undergoing simultaneous coronary and carotid artery surgery present with a high incidence of postoperative cognitive dysfunction (POCD) in the early postoperative period (Maleva et al, 2019(Maleva et al, , 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Although this procedure is not always complicated by traumatic brain injury (stroke), it may cause a less pronounced, diffuse lesion that later leads to cognitive decline (Weimar et al, 2017;Maleva et al, 2020). Previous studies have shown that patients undergoing simultaneous coronary and carotid artery surgery present with a high incidence of postoperative cognitive dysfunction (POCD) in the early postoperative period (Maleva et al, 2019(Maleva et al, , 2020.…”
Section: Introductionmentioning
confidence: 99%